2018
DOI: 10.2485/jhtb.27.219
|View full text |Cite
|
Sign up to set email alerts
|

Demineralized Dentin Matrix as a Carrier of Recombinant Human Bone Morphogenetic Proteins: <i>in Vivo</i> Study

Abstract: This study aimed to evaluate the effi cacy of rabbit demineralized dentin matrix (DDM) as a recombinant human bone morphogenetic protein-2 (rhBMP-2) carrier using the subcutaneous tissues of mice and rabbit calvarial critical-sized defects. DDM of rabbit, combined with rhBMP-2 (DDM/rhBMP-2) was transplanted into the subcutaneous tissues of 6 mice and 6 rabbit calvarial critical-sized defects (DDM = 0.03 g, control; DDM/rhBMP-2 = 0.03 g of DDM, 0.2 mg/ml, 5.0 μg of rhBMP-2, experimental). Both DDM and DDM/rhBMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 50 publications
(67 reference statements)
0
34
1
Order By: Relevance
“…However, the amount of bone formation 3‐6 months after the graft is noteworthy (34.39% in the DDM/rhBMP‐2 group and 29.75% in the DDM group) considering that the concentration of rhBMP‐2 used in this study was 0.2 mg/mL, which is approximately seven times lower than the presently approved concentration. The amount of bone formation 4 weeks after grafting in a rabbit calvarial defect model was reported to be greater in a group that was treated with DDM/rhBMP‐2 0.2 mg/mL than in a group that was treated with DDM alone (47.99% vs 24.94%) …”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…However, the amount of bone formation 3‐6 months after the graft is noteworthy (34.39% in the DDM/rhBMP‐2 group and 29.75% in the DDM group) considering that the concentration of rhBMP‐2 used in this study was 0.2 mg/mL, which is approximately seven times lower than the presently approved concentration. The amount of bone formation 4 weeks after grafting in a rabbit calvarial defect model was reported to be greater in a group that was treated with DDM/rhBMP‐2 0.2 mg/mL than in a group that was treated with DDM alone (47.99% vs 24.94%) …”
Section: Discussionmentioning
confidence: 93%
“…The amount of bone formation 4 weeks after grafting in a rabbit calvarial defect model was reported to be greater in a group that was treated with DDM/rhBMP-2 0.2 mg/mL than in a group that was treated with DDM alone (47.99% vs 24.94%). 17 Along with the superior effects of BMP-2/ACS in preclinical models, clinical studies have demonstrated successful results There was less residual dentin after treatment with DDM/rhBMP-2 than after treatment with DDM alone; however, the difference was not statistically significant. Experimental studies of human dentin grafts in a rabbit model showed that the remodeling resorption process involves continuous resorption of dentin with bone replacement in the dentin resorption cavities after 6 months.…”
Section: Histomorphometric Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…26 Three other studies used DDM dipped into the rhBMP-2 solution and freeze-dried as a single composite. [27][28][29] In clinical studies, 29-31 the rhBMP-2 concentration within DDM/rhBMP-2 was set at 0.2 mg/mL, which is lower than the FDAapproved concentration of 1.5 mg/mL 1 .…”
Section: Preparation Of Demineralized Dentin Matrix As a Carrier Formentioning
confidence: 99%